A quality improvement project addressing the underreporting of delirium in hip fracture patients. (November 2022) - Onizuka, Naoko; Huyke-Hernández, Fernando A.; Roby, Myriam A.; Martell, Tom F.; Scislow, Rachael M.; Jones, Sarah C.; Olson, Andrew; James, Nicole; Switzer, Julie A.
Abstract: Introduction: After discovering a low incidence of delirium for hip fracture patients at our institution, we evaluated if this was due to underreporting and, if so, where process errors occurred. Methods: Hip fracture patients aged ≥60 with a diagnosis of delirium were identified. Chart-Based Delirium Identification Instrument (CHART-DEL) identified missed diagnoses of delirium. Process maps were created based off staff interviews and observations. Results: The incidence of delirium was 15.3% (N = 176). Within a random sample (n = 98), 15 patients (15.5%) were diagnosed, while 20 (24.7%) went undiagnosed despite evidence of delirium. Including missed diagnoses, delirium prevalence was higher in the sample compared to all patients (35.7% vs 15.3%, p < 0.001). Most missed diagnoses were due to failure in identifying delirium (60%) or failure in documenting/coding diagnosis (20%). The prevalence of baseline cognitive impairment was higher in undiagnosed delirium patients versus correctly diagnosed patients (80% vs 20%, p = 0.001). Conclusions: Our institution significantly underreports delirium among hip fracture patients mainly due to; (1) failure to identify delirium by the clinical staff, and (2) failure to document/code diagnosis despite correct identification. Baseline cognitive impairment can render delirium diagnosis challenging. These serve as targets for quality improvement and hip fracture care enhancement.